2016
DOI: 10.3346/jkms.2016.31.7.1100
|View full text |Cite
|
Sign up to set email alerts
|

Febrile Urinary Tract Infection after Radical Cystectomy and Ileal Neobladder in Patients with Bladder Cancer

Abstract: Urinary tract infection (UTI) is one of the most common complications after radical cystectomy and orthotopic neobladder reconstruction. This study investigated the incidence and implicated pathogen of febrile UTI after ileal neobladder reconstruction and identify clinical and urodynamic parameters associated with febrile UTI. From January 2001 to May 2015, 236 patients who underwent radical cystectomy and ileal neobladder were included in this study. Fifty-five episodes of febrile UTI were identified in 46 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…In this study, the overall prevalence of asymptomatic bacteriuria in cancer confirmed patients was 23.3%. is finding of bacteriuria was in line with the reports in Korea (23.5%) [26] and India (20.1%) [27]. However, a higher prevalence of bacteriuria was reported in this study than the studies conducted in Texas (15%), Sweden (5%), and Japan (15%) [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the overall prevalence of asymptomatic bacteriuria in cancer confirmed patients was 23.3%. is finding of bacteriuria was in line with the reports in Korea (23.5%) [26] and India (20.1%) [27]. However, a higher prevalence of bacteriuria was reported in this study than the studies conducted in Texas (15%), Sweden (5%), and Japan (15%) [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, catheterization and previous surgery and other independent variables were not significantly associated with bacteriuria. Consistently, surgery had been found to be less important in a study by Kim et al in patients with bladder cancer [41]. In our study, the effect of ampicillin, augmentin, tetracycline, and penicillin were minimal while cefoxitin, International Journal of Microbiology nitrofurantoin, norfloxacin, nalidixic acid, and ciprofloxacin were found to be the most efficient antibiotics for bacterial isolates from both cancer patients and apparently healthy blood donors.…”
Section: Discussionsupporting
confidence: 88%
“…Rates of early post-operative bacteremia, SSI and UTI (< 30 days) in other studies varied between 5 to 17%, 8 to 33% and 4 to 36%, respectively. [5, 911] One explanation for the large differences in reported incidences of post-operative infections after radical cystectomy might be the different types of antibiotic prophylaxis regimens used in different studies. Pariser et al showed that type of peri-operative antibiotic prophylaxis regimen might have significant effect on infection outcomes after radical cystectomy [7], which was also found in two other studies that analyzed post-operative infections within 90 days after UDS [14, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Of these infectious complications, bacteremia was reported in 5 to 17% of the patients [911], cUTI was reported in 4 to 36% of the patients [5, 911] and SSI was reported in 8 to 33% of patients [4, 69, 11] after UDS, even when peri-operative antimicrobial prophylaxis was used. Although some of these studies reported on the causative bacteria [4, 5, 8–10], we found that only a few studies partially provided information on antimicrobial susceptibility of the cultured bacteria [4, 8, 9]. Particularly in the era of increasing antimicrobial resistance, susceptibility profiles provide an important pillar in the correct use of antimicrobial prophylaxis [7, 12].…”
Section: Introductionmentioning
confidence: 99%
“…The IONB was constructed using the Studer technique; the surgical procedure was described previously. [13] Ultimately, 287 patients with a Studer IONB after RC were analyzed.…”
Section: Methodsmentioning
confidence: 99%